On multi-objective linear programming problems with inexact rough interval-fuzzy coefficients - Ammar, E. E.; Hussein, M. L.; Khalifa, A. M. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
This paper deals with a multi-objective linear programming problem with an inexact rough interval fuzzy coefficients IRFMOLP. This problem is considered by incorporating an inexact rough interval fuzzy number in both the objective function and constrains. The concept of "Rough interval" is introduced in the modeling framework to represent dualuncertain parameters. A suggested solution procedure is given to obtain rough interval solution for IRFLP(w) problem. Finally,two numerical example is given to clarify the obtained results in this paper.